Salt Stress Affects Plastid Ultrastructure and Photosynthetic Activity but Not the Essential Oil Composition in Spearmint (Mentha spicata L. var. crispa “Moroccan”) - Ounoki, Roumaissa; Ágh, Ferenc; Hembrom, Richard; Ünnep, Renáta; Szögi-Tatár, Bernadett; Böszörményi, Andrea; Solymosi, Katalin (Frontiers in Plant Science, 2021)
High levels of soil salinity affect plant growth, reproduction, water and ion uptake, and plant metabolism in a complex manner. In this work, the effect of salt stress on vegetative growth, photosynthetic activity and chloroplast ultrastructure of spearmint (Mentha spicata L. var. crispa ‘Moroccan’) was investigated. After 2 weeks of low concentration treatments (5, 25 and 50 mM NaCl) of freshly cut shoots we observed that at 50 mM NaCl concentration, the stem-derived adventitious root formation – a major mean for vegetative reproduction among mints – was completely inhibited. One-week-long, high concentration (150 mM NaCl) salt stress and isosmotic polyethylene glycol (PEG) 6000 treatments were compared in intact (rooted) plants and freshly cut (i.e. rootless) shoots. Our data showed that roots have an important role in mitigating the deleterious effects of both the osmotic (PEG treatment) and specific ionic components of high salinity stress. At 50 mM NaCl or above, the ionic component of salt stress caused strong and irreversible physiological alterations: decrease in relative water content, maximal and actual quantum efficiency of photosystem II, relative chlorophyll content, as well as disorganization of the native chlorophyll-protein complexes as revealed by 77K fluorescence spectroscopy. In addition, important ultrastructural damage was observed by transmission electron microscopy such as the swelling of the thylakoid lumen at 50 mM NaCl treatment. Interestingly, in almost fully dry leaf regions and leaves, granum structure was relatively well retained, however, their disorganization occurred in leaf chloroplasts of rooted spearmint treated with 150 mM NaCl. This loss of granum regularity was also confirmed in the leaves of these plants using small-angle neutron scattering measurements of intact leaves of 150 mM NaCl-stressed rooted plants. At the same time, solid-phase microextraction of spearmint leaves followed by gas chromatography and mass spectrometry analyses revealed that the essential oil composition of spearmint was unaffected by the treatments applied in this work. Taken together, the used spearmint cultivar tolerates low salinity levels, however, at 50 mM NaCl concentration and above, the ionic components of the stress strongly inhibit adventitious root formation and thus clonal propagation in them, and severely damage the photosynthetic apparatus.